2020
DOI: 10.3390/polym12010237
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Analysis and Characterization of Novel and Environmentally Friendly Feather Protein-Based Wood Preservatives

Abstract: In this study, feather was used as the source of protein and combined with copper and boron salts to prepare wood preservatives with nano-hydroxyapatite or nano-graphene oxide as nano-carriers. The treatability of preservative formulations, the changes of chemical structure, micromorphology, crystallinity, thermal properties and chemical composition of wood cell walls during the impregnation and decay experiment were investigated by retention rate of the preservative, Fourier transform infrared spectroscopy (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Xia et al [35] used feather as a source of protein in combination with copper and boron salts, and they made wood preservatives using nano-hydroxyapatite or nano-graphene oxide as nano-carriers. The results revealed that the penetration into the wood structure was successful, and it was concluded, based on the decay experiments, that the protein-based preservatives had the potential to be considered as a low-cost and environmental friendly alternative for wood preservation.…”
mentioning
confidence: 99%
“…Xia et al [35] used feather as a source of protein in combination with copper and boron salts, and they made wood preservatives using nano-hydroxyapatite or nano-graphene oxide as nano-carriers. The results revealed that the penetration into the wood structure was successful, and it was concluded, based on the decay experiments, that the protein-based preservatives had the potential to be considered as a low-cost and environmental friendly alternative for wood preservation.…”
mentioning
confidence: 99%
“…Nonetheless, the leaching rates in new preservative formulations containing copper, such alkaline copper quaternary (ACQ) and copper boron azole (CBA), are at least 10 times higher than CCA. , The leaching of these preservatives causes groundwater and soil contamination. Additionally, the currently available water-soluble, organic preservatives are either not potent enough and need to be paired with a secondary preservative, such as the copper azole type c (CA-C) preservative, or require high concentrations, such as in the case of boron-based preservatives, which are prone to leaching . Organic triazoles, such as propiconazole and triadimefon, are approved by the U.S. EPA for use in above ground applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, though propiconazole has demonstrated antifungal activity, it has modest solubility in water, which limits its concentration in water-borne preservative systems. There is a need for low-cost, bio-based, effective, nonhazardous, and biologically and environmentally friendly preservatives that easily penetrate and fixate to the wood …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few ways researchers have been able to resolve the issue of leaching is by enzymatic polymerization of wood extractives with the lignin contained in the wood [9] and, by employing nanoparticles [10]. However, there is still a need for low-cost, effective, non-hazardous, biologically and environmentally friendly preservatives that easily penetrate the wood [11].…”
Section: Motivationmentioning
confidence: 99%